2005
DOI: 10.1074/jbc.m510391200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Nonstructural Proteins Inhibit Apolipoprotein B100 Secretion

Abstract: Host genes involved in lipid metabolism are differentially regulated during the early stages of hepatitis C virus (HCV) infection. The majority of lipids synthesized in the liver are exported to other tissues in the form of lipoproteins. The formation of these lipoproteins is dependent upon the association of triglycerides with apolipoprotein B100. Using the HCV subgenomic replicon expression system, we show that secretion of apoB100 is significantly reduced. Inhibition of apoB100 degradation by ALLN did not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 60 publications
(74 reference statements)
5
48
1
Order By: Relevance
“…These vesicular structures were not prominent when we stained control Huh7 cells with anti-apoB, suggesting that these structures may be induced by the viral NS proteins as reported (28). Diversion of nascent VLDL to these structures might explain the previous reports that HCV infection decreases the rate of VLDL secretion in patient (29) and Huh7 cells (30). The vesicles containing the HCV replication complex appears to be derived from the ER because apoB in the vesicles is endo H-sensitive (SI Fig.…”
Section: Discussionmentioning
confidence: 56%
“…These vesicular structures were not prominent when we stained control Huh7 cells with anti-apoB, suggesting that these structures may be induced by the viral NS proteins as reported (28). Diversion of nascent VLDL to these structures might explain the previous reports that HCV infection decreases the rate of VLDL secretion in patient (29) and Huh7 cells (30). The vesicles containing the HCV replication complex appears to be derived from the ER because apoB in the vesicles is endo H-sensitive (SI Fig.…”
Section: Discussionmentioning
confidence: 56%
“…The principal role of MTP is to facilitate the transfer of lipids to the nascent apoB-containing lipoprotein particle, which is then converted to VLDL by the addition of lipid droplets (26)(27)(28)(29). Although MTP is capable of transferring the four major lipid classes (free cholesterol, phospholipids, TG, and cholesteryl esters), this transfer protein strongly prefers TG and cholesteryl esters (30). Previous studies have shown that a defective mutation in MTP causes a b lipoproteinemia characterized by the absence of apoB lipoproteins accompanied by fatty liver disease (31).…”
Section: Discussionmentioning
confidence: 99%
“…APOB is a protein that is part of the lipoprotein family and one that largely moves cholesterol around the body. A study found that proteins involved in the virus' progression inhibit the secretion of the APOB protein; the significance of the finding is that it provides evidence that HCV alters the lipid structure throughout the body (Domitrovich et al, 2005). The complement system, a group of proteins with a role in the immune system, naturally is important to both HIV/HCV pathogenesis and treatment.…”
Section: Discussionmentioning
confidence: 99%